Compare the Efficacy of Oral Versus Intravenous Medicine in Treatment of Spontaneous Bacterial Peritonitis - Sarwar Khan, Tahira Inam, Kapeel Raja, Rahila Ali, Furhaj Mueen Siddique, Kiran Fatima, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to determine whether or not oral medication is more effective than intravenous medication in the treatment of peritonitis caused by bacteria. Study Design:Comparative study Place and Duration: Department of Internal Medicine Gangaram hospital Lahore and Medical ward, THQ Hospital Dargai, from October, 2021 to March, 2022. Methods: There were 102 cases of both genders having spontaneous bacterial peritonitis because of cirrhosis were included. Included patients were aged between 18-60 years.After taking informed written consent, detailed demographics of enrolled cases were recorded. Patients were equally divided in two groups. Group I received intravenous antibiotic in 51 patients and group II received oral antibiotics in 51 patients. Post-treatment outcomes were compared among both groups. SPSS 22.0 was used to analyze all data. Results: We found that effectiveness in group I was higher 47 (92.2%) as compared to group II44 (86.3%) but not a significant difference observed. Frequency of mortality in group II was 4 (7.8%) and in group I 3 (5.9%). Diarrhea, nausea, vomiting, rashes and gastrointestinal distress were the most common adverse effects in both groups. Conclusion: We concluded in this study that the use of antibiotics orally and intravenously for SBP treatment was affective equally. There was no any significant difference observed in both procedures. Keywords: Cirrhosis, Oral Antibiotics, Intravenous Antibiotics, SBP, Efficacy